Samomor in Cankarjev roman Martin Kačur - Zupan Sosič, Alojzija (Ars et humanitas, 2022)
Suicide is still a taboo topic in Slovenia, despite the high rate of suicide, so I focused on it in more detail in the review of philosophical positions and classifications of voluntary death. In the interpretative-analytical research, I justified Kačur‘s death in Cankar’s novel Martin Kačur as a suicide, which I considered from different perspectives. I took into account Schopenhauer’s philosophical tolerance of suicide through the ethics of compassion, Nietzsche’s justification of suicide as an expression of human freedom in the world, Freud’s explanation of the link between the instinct of death and life, and three levels of philosophical belief or mood. These are idealism, nihilism and fatalism, arranged in a constant dialogic relationship, through which we pass from the story to the narrative level. Taking into account realistic (the gradual decline of Kačur) and symbolist poetics (the hallucinatory logic of symbols), I used different classifications to prove suicide, according to which Kačur’s suicide is a subtle combination of egoistic or selfish and logical or nihilistic and meek and unconscious suicide. While the connection between the egoistic and the logical suicide philosophically justifies Kačur’s decision, the combination of involuntary and meek suicide affects the reader’s empathy. With her help, we try not to understand the tragic downfall of the altruistic Kačur, similar to most of Cankar’s main characters, only through the thematization of the unfortunate idealist, but also through the special poetics of (Austrian) modernity, which paid special attention to death at the beginning of the 20th century.
Keywords: ethics of compassion; etika sočutja; idea of free death; ideja svobodne smrti; Nietzsche, Friedrich; novel as a triptych; roman kot triptih; samomor; Schopenhauer, Arthur; Slovene literature; Slovene novels; Slovene writers; slovenska književnost; slovenski pisatelji; slovenski romani; social empathy; socialna empatija; suicide